EMPLOYEE PERFORMANCE EFFECTIVENESS IN DELIVERING PUBLIC SERVICES AT ORGANIZATION BUREAU OF THE REGIONAL SECRETARIAT EAST JAVA PROVINCE - Odisti Zulfa Intifadah; V. Rudy Handoko; Achluddin Ibnu Rochim (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2023)
The government carried out bureaucratic reforms to realize good governance. The effectiveness of a government system is determined by the merits of public service delivery. Work effectiveness is the basis for employees to carry out program tasks and activities so that the implementation goes on target and optimally. This study aims to describe the process of implementing public services from an employee's perspective as well as describe and analyze the constraints and describe the solutions undertaken to increase the effectiveness of the work of employees in the Organizational Bureau of the Regional Secretariat of East Java Province. The type of research used is descriptive qualitative. Data analysis used is data reduction, presentation, and conclusion. Data collection methods include interviews, observation and documentation. The results of the study obtained an overall picture that the effectiveness of employee work in realizing public services at the Regional Secretariat Organizational Bureau of East Java Province is already good, employee work results can be proven by Employee Work Targets which meet the target every month but are not optimal due to a shortage of employees and less use of working time.